K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

28 tháng 6 2021

x + x + x = 12 - 11 + 35

x + x + x = 36

x             = 36 : 3

x             = 12

Vậy x = 12

Học tốt!!!

28 tháng 6 2021

x + x + x = 12 - 11 + 35

3x = 1 + 35

3x = 36

x = 36 : 3

x = 12

I
3 tháng 6 2016

  3x8x76+2x35x12-4x11x6

= 24x76+24x35-24x11

= 24x(76+35-11)

=24x100

= 2400

3 tháng 6 2016

3 x 8 x  76 + 2 x 35 x 12 - 4 x 11 x 6

= ( 3 + 2 ) x ( 8 + 35 ) x ( 76 + 12 )  - 4 x 11 x 6

= 5 x 43 x 88 - 4x 11 x 6

= ( 5-4 ) x ( 43 - 11 ) x ( 88 - 6 )

= 1 x 32 x 82

= 2624

23 tháng 3 2022

B

23 tháng 3 2022

b

10 tháng 6 2021

đáp án b nha bạn

10 tháng 6 2021

132 + 77 + 198 

= 11 x 12 + 11 x 7 + 18 x 11 

= 11 x ( 12 + 7 + 18 ) 

= 11 x 37 

B

3 tháng 10 2021

a, \(2\frac{5}{12}+x=3\frac{1}{6}\) 

=> x = \(3\frac{1}{6}-2\frac{5}{12}\) 

x = ( 3 - 2 ) + ( 1/6 - 5/12 )

x = 1 + ( -1/4 ) => x = 3/4 

b, 26/35 : x = 2 

=> x = 26/35 : 2

=> x = 26/35 . 1/2 

=> x  = 13/35

c, x -3/5 =11/15

x = 11/15  + 3/5 

x= 11/15 + 9/15 => x= 20/15 => x = 4/3

d, \(2\frac{7}{8}.x=1\)

> x = 1 : \(2\frac{7}{8}\)  => x = 1: 23/8  => x = 1. 8/23 => x = 8/23 

3 tháng 10 2021

a) 

x = 31/6 - 25/12

x = 37/12

b)

x = 26/35 : 2

x = 13/35

c)

x = 11/15 + 3/5

x = 4/3

d) 

x = 1 : 27/8

x = 27/8

22 tháng 6 2023

a) \(6x+15\times8=12\times\left(19-x\right)\)

\(6x+120=228-12x\)

\(6x+120-228+12x=0\)

\(18x-108=0\)

\(18x=108\)

\(x=6\)

b) \(160-\left(35\div x+3\right)\times15=15\)

\(160-\left(35\div x+3\right)=1\)

\(35\div x+3=159\)

\(35\div x=156\)

\(x=\dfrac{35}{156}\)

22 tháng 6 2023

c) \(2x-\left(1309\div11-19\right)-2=0\)

\(2x-1309\div11-19=2\)

\(2x-119-19=2\)

\(2x-119=21\)

\(2x=140\)

\(x=70\)

d) \(\left(x-7\right)\times\left(2x-16\right)=0\)

\(x-7=0;2x-16=0\)

\(x=7;2x=16\)

\(x=7;x=8\)

 

22 tháng 7 2019

a)\(\frac{27}{5}\text{x}\frac{91}{12}\text{x}\frac{125}{9}\text{x}\frac{96}{13}=\frac{27}{9}\text{x}\frac{91}{13}\text{x}\frac{125}{5}\text{x}\frac{96}{12}=3\text{x}7\text{x}25\text{x}8\)

Đến đây tự tính nha !

b)\(\frac{2539}{35}\text{x}\frac{7}{90}+\frac{561}{35}\text{x}\frac{7}{90}=\frac{7}{90}\text{x}\left(\frac{2539}{35}+\frac{561}{35}\right)=\frac{7}{90}\text{x}\frac{3100}{35}=\frac{3100}{90}\text{x}\frac{7}{35}=\frac{310}{9}\text{x}\frac{1}{5}=\frac{62}{9}\)

28 tháng 2 2020

1. 27/5 x 91/12 x 125/9 x 96/13

2. 2539/35 x 7/90 + 561/35 x 7/90

3. 31/7 : (2/5 x 31/7)

4. (29 x 15/23 x 36/29) : 5/23

12 tháng 10 2021

Câu 2: 

\(\dfrac{7}{9}\cdot\dfrac{3}{35}=\dfrac{1}{5}\cdot\dfrac{1}{3}=\dfrac{1}{15}\)

\(\dfrac{9}{22}\cdot55=\dfrac{9\cdot55}{22}=\dfrac{9\cdot5}{2}=\dfrac{45}{2}\)

 

12 tháng 10 2021

???gianroi

19 tháng 8 2023

123,45 + 23,56 +76,44 + 54,55

= (123,45 + 54,55) + (23,56 + 76,44)

= 178 + 100

= 278

456 x 45 + 456 x 10 + - 456 x 55

=456 x (45 +10-55)

=456 x 0

=0

19 tháng 8 2023

2,5 x 8,5 + 7,5 x 8,5 

=8,5 x (2,5 +7,5)

= 8,5 x 10

= 85

86 x 5 + 86 x 4 + 86

= 86 x (5+4+1)

= 86 x10

860

17 tháng 1 2018

1, 2x - 35 = 15

  2x         =  15 + 35

  2x         =   50

    x         =  50 : 2 

    x         =   25.

2, 3x + 18 = 12

    3x        =  12 - 18

    3x        = -6

     x         =  -6 : 3

     x         =  -2.

3, / x - 1 / = 0

=> x \(\in\varnothing\).

4, -13 /x/ = - 26

  /x/        = -26 : -13

=> \(\orbr{\begin{cases}x=2\\x=-2\end{cases}}\)

 Vậy x \(\in\){ 2 ; -2}.

5,4 - ( 27 - 3 ) = x - ( 13 - 4 )

  4 - 24           = x - 9

  -20               =  x - 9

             -x      =    9 + 20

             -x      =    29

              x      =   -29.

6, 47 - ( x + 15 ) = 21

  47 - x - 15        = 21

       -x - 15         = 21 - 47 

       -x - 15         = -26

             -x          =  -26 + 15 

             -x          =     - 11

              x          = 11.

7, -5 -( 24 - x) = - 11

   -5 - 24 + x   = -11

        -24 + x   = -11 + 5

        -24 + x   =  -6

                 x   = -6 + 24

                 x   =  18.

8, 6 - /x/ = 2

        /x/   = 6 - 2

         \(\orbr{\begin{cases}x=3\\x=-3\end{cases}}\)

Vậy x \(\in\left\{3;-3\right\}.\)

9, 6 + /x/ = 2

         /x/ = 2 - 6

=>      x = -4.

17 tháng 1 2018

2x - 35 = 15

=> 2x = 15 + 35

=> x = 50 : 2

=> x = 25

3x + 18 = 12

=> 3x = 12 - 18

=> x = ( -6 ) : 3

=> x = -2

| x - 1 | = 0

=> x - 1 = 0

=> x = 0 + 1

=> x = 1

-13 * | x | = -26

=> | x | = -26 : ( -13 )

=> | x | = 2